MENINGKATKAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS MENGGUNAKAN METODE COOPERATIVE TIPE STAD DI SD - Sari, Ivana (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
Basicly, this research of write observasion especially class V SDN 01  Lembah Melintang. This research to describe the result of student learning which use cooperative type STAD in class V. The near research using cualitatif and cuantitatif with kind of class act result of RPP ciclus I meeting I and II is 78,57% and 82,14%. Ciclus II meeting I and II is 85,71% and 96,42% from the teacher seeing ciclus I meeting I and II  is 66,6% , 75%, ciclus II meeting I and II is 83,3%, 87,5%. Result of student ciclus I meeting I and II is 62,5%,70,8%. Ciclus II meeting I and II is 79,1%, 83,3%. Result of student learning, ciclus I meeting I and II is 62,96, 67,8. Ciclus II meeting I and II 78,05, 88,46. From the result of this researches can conclude is to using cooperative type STAD of activitas and learning student IPS class V in SDN 01 Lembah Melintang kabupaten Pasaman Barat  can be good rating.   Kata kunci: hasil belajar, IPS SD, model cooperative learning tipe STAD.